2011
DOI: 10.1002/wrna.115
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of RNAs: exosomes as mediators of intercellular communication

Abstract: Multicellular organisms are similar to biological communities, consisting of various cell types; thus, inter-cell communication is critical for the functioning of the whole system that ultimately constitutes a living being. Conventional models of cellular exchange include signaling molecules and direct contact-mediated cell communications. Exosomes, small vesicles originating from an inward budding of the plasma membrane, represent a new avenue for signaling between cells. This interchange is achieved by packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
122
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 68 publications
3
122
0
Order By: Relevance
“…Although it is considered that there is a selective loading of specific mRNA and miRNA molecules into exosomes, its mechanism is not clear and further investigation is necessary. 30) In our study, pcRNAs and the parental genes of the pseudogenes were highly coincident in exosomes I, II and WS. Recent studies showed that transcribed pseudogenes can regulate the translation of homologous protein-coding genes, such as mRNAs of their parental gene, by an small interfering RNA (siRNA)-like function and/or miRNA sponge.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although it is considered that there is a selective loading of specific mRNA and miRNA molecules into exosomes, its mechanism is not clear and further investigation is necessary. 30) In our study, pcRNAs and the parental genes of the pseudogenes were highly coincident in exosomes I, II and WS. Recent studies showed that transcribed pseudogenes can regulate the translation of homologous protein-coding genes, such as mRNAs of their parental gene, by an small interfering RNA (siRNA)-like function and/or miRNA sponge.…”
Section: Discussionsupporting
confidence: 54%
“…The mRNAs contained within exosomes can be transcribed into cDNA or translated in the recipient cell. 30) However, further study will be needed to elucidate whether the pcRNAs in salivary exosomes are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes contain a complex mixture of miRs, mRNAs, and proteins, and their ability to traverse the intercellular space and to be taken up by neighboring cells is becoming increasingly recognized as an important mechanism for delivering genetic, epigenetic, or proteomic information from donor cells and effecting functional modifications in recipient cells. 11,19,60,61 Whereas most previous studies have focused on these mechanisms as they relate to exosomal pathways in cancer and immune cells, including HCCs, 15,17,18 emerging evidence from this and other laboratories has revealed that fibrogenic cells are also regulated by exosomal networks. 10,22,23,31,34 In addition to revealing that miR-199a-5p targets the CCN2 3 0 -UTR in the same cells as which it is produced, the studies reported here indicate that miR199a-5p is released from HSCs in exosomes and that exosomal miR-199a-5p concentrations reflect those of their producer cells, being expressed at high levels in exosomes from quiescent HSCs and at low levels in exosomes from activated HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Exosomes, produced by most if not all cells of the body, are nanosized membranous vesicles that are capable of delivering complex molecular payloads to recipient cells, which may become functionally reprogrammed according to the molecular cues received. 11e13 HepG2 hepatoblastoma cells were the first liver cell type for which exosome production was documented, 14 and recent reports have described exosomal pathways for a variety of hepatic cancer cells that result in delivery of RNAs or proteins and subsequent regulation of cancer cell proliferation, chemosensitivity or migration, 15e18 intercellular transmission of the hepatitis C virus, 19 or acquisition of a proangiogenic phenotype by endothelial cells. 20,21 However, a more expansive and highly complex role for exosomes in the liver is now emerging, with the recognition that a broad variety of hepatic cells, including hepatocytes, macrophages, cholangiocytes, and HSCs, produce exosomes that can influence a broad spectrum of cellular processes involved in liver repair after hepatectomy or pathogenesis associated with fibrosis, alcoholic liver disease, nonalcoholic steatohepatitis, or nonalcoholic fatty liver disease.…”
mentioning
confidence: 99%
“…Since the first report demonstrating the presence of mRNA and microRNA in exosome preparations (Valadi et al , 2007 ), thousands of different mRNAs may be identified in exosomes derived from murine and human cells. Interestingly, some hundreds of gene transcripts were exclusively detectable in MVs/ exosomes and not in the cellular source of exosomes (Hu et al , 2012 ;L ä sser, 2012 ;Ramachandran and Palanisamy , 2012 ). This suggests that specific selection mechanism/s operate during the intracellular sorting of RNAs into exosomes (Valadi et al , 2007 ;Taylor and Gercel -Taylor, 2008 ;Rabinowits et al , 2009 ;Mittelbrunn et al , 2011 ).…”
Section: Nucleic Acidsmentioning
confidence: 99%